Pengungkapan Emisi Karbon Perusahaan Energi di Indonesia - Sandy, Kadek Egiana; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2023)
This research aims to determine the factors that influence the disclosure of carbon emissions by energy companies in Indonesia. This research examines 34 sustainability reports published by energy companies listed on the Indonesia Stock Exchange in 2018 and 2019. Content analysis is used to test the extent of carbon emissions disclosure, namely the size of the dependent variable in this research. Profitability and perceived environmental reputation are operated as independent variables while environmental performance, company size, company age, and government ownership are operated as control variables in this study. Legitimacy theory is used to explain research findings. To achieve the research objectives, this research uses multiple linear regression analysis. The results of the analysis show that profitability has no significant effect on carbon emissions disclosure, while perceived environmental reputation has a significant effect on carbon emissions disclosure. Keywords: Carbon Emission Disclosure; Energy of Companies; Profitability; Perceived Reputation; Legitimacy Theory